2018
DOI: 10.1038/s41467-018-04622-w
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent point mutation in PRKCA is a hallmark of chordoid gliomas

Abstract: Chordoid glioma (ChG) is a characteristic, slow growing, and well-circumscribed diencephalic tumor, whose mutational landscape is unknown. Here we report the analysis of 16 ChG by whole-exome and RNA-sequencing. We found that 15 ChG harbor the same PRKCAD463H mutation. PRKCA encodes the Protein kinase C (PKC) isozyme alpha (PKCα) and is mutated in a wide range of human cancers. However the hot spot PRKCAD463H mutation was not described in other tumors. PRKCAD463H is strongly associated with the activation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 68 publications
(79 reference statements)
0
33
0
Order By: Relevance
“…The PRKCA D463H mutation has not been reported in other tumors, suggesting that it is a diagnostic hallmark for chordoid gliomas . However, different alterations in the PRKCA gene have been reported in two other CNS tumor entities; PRKCA D294G mutations in pituicytomas and the SLC44A1‐PRKCA gene fusions in papillary glioneuronal tumors .…”
Section: Low‐grade Pediatric Gliomas Mixed Glioneuronal Neoplasms Amentioning
confidence: 99%
See 2 more Smart Citations
“…The PRKCA D463H mutation has not been reported in other tumors, suggesting that it is a diagnostic hallmark for chordoid gliomas . However, different alterations in the PRKCA gene have been reported in two other CNS tumor entities; PRKCA D294G mutations in pituicytomas and the SLC44A1‐PRKCA gene fusions in papillary glioneuronal tumors .…”
Section: Low‐grade Pediatric Gliomas Mixed Glioneuronal Neoplasms Amentioning
confidence: 99%
“…Rosenberg et al. recently investigated 16 such tumors by whole‐exome and RNA sequencing and found that 15 cases harbored the same PRKCA D463H mutation. PRKCα is involved in a wide range of cellular processes, and can both act as a tumor suppressor and an oncogene.…”
Section: Low‐grade Pediatric Gliomas Mixed Glioneuronal Neoplasms Amentioning
confidence: 99%
See 1 more Smart Citation
“…This rare tumor always expresses a missense mutation of the gene encoding proteinase K (PRKCA). Substrate analysis of this enzyme opens up targeted therapeutic perspectives . Metabolic studies offer other perspectives: oxidative metabolism is increased in glioma cells with a FGFR3‐TACC3 fusion and treatments directed against oxidative stress like metformin can induce tumor cell death …”
Section: Present and Prospect: Neuropathology And Neurosciencesmentioning
confidence: 99%
“…In our previous study, it was demonstrated that HDGF mRNA was highly expressed in LADC tissues and that increased HDGF levels promoted PRKCA expression by inhibiting miR-296-3p in LADC cells (11). PRKCA is a member of the PKC family, and upregulation of PRKCA has been reported in several types of cancer and has been found to regulate various cellular functions, including cell proliferation, survival and metastasis (15)(16)(17)(18). Although HDGF and PRKCA overexpression plays a pivotal role in NSCLC progression, the association between HDGF and PRKCA and clinical characteristics, as well as the prognostic effect of combined HDGF and PRKCA expression are not understood in LADC.…”
Section: Introductionmentioning
confidence: 99%